2004
DOI: 10.1182/blood-2003-09-3146
|View full text |Cite
|
Sign up to set email alerts
|

In vivo exit of c-kit+/CD49dhi/β7+ mucosal mast cell precursors from the bone marrow following infection with the intestinal nematode Trichinella spiralis

Abstract: We have used the parasite helminth Trichinella spiralis to study the generation and differentiation of mast cell progenitors in the bone marrow of mice, as this infection triggers an intestinal mastocytosis which correlates with parasite expulsion. C-kit ؉ mast cell progenitors have previously been defined by methylcellulose colony-forming units and by limiting dilution assays in vitro. In vivo experiments have demonstrated the essential requirement by mast cells for specific integrin expression. We have defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 34 publications
(43 reference statements)
2
40
0
Order By: Relevance
“…1, A and B), both of which were Ͼ90% Fc⑀RI ϩ /c-kit ϩ using flow cytometric analysis. We confirmed the expression of integrin ␣ 4 (11,13,30,46,47), ␣ 5 (5,11,26,28,30), ␣ V (12), ␣ L (48, 49), ␤ 1 (11,26), ␤ 2 (50), and ␤ 3 (12), as reported (Fig. 1A).…”
Section: Bmmc and Pmc Express Integrinsupporting
confidence: 70%
See 1 more Smart Citation
“…1, A and B), both of which were Ͼ90% Fc⑀RI ϩ /c-kit ϩ using flow cytometric analysis. We confirmed the expression of integrin ␣ 4 (11,13,30,46,47), ␣ 5 (5,11,26,28,30), ␣ V (12), ␣ L (48, 49), ␤ 1 (11,26), ␤ 2 (50), and ␤ 3 (12), as reported (Fig. 1A).…”
Section: Bmmc and Pmc Express Integrinsupporting
confidence: 70%
“…Accumulating evidence revealed that several kinds of integrins were involved in the migration of mast cells (13,37,47,50), and that the interaction between SCF and c-kit regulated the migration of mast cells via ECM proteins, especially FN (13, 14, 37, 47, 50, 52). We examined SCF-induced migration of mast cells via fibrinogen, and then tested whether integrin ␣ IIb ␤ 3 -fibrinogen interaction would induce migration.…”
Section: Scf Induced Integrin ␣ Iib ␤ 3 -Directed Migration Of Mast Cmentioning
confidence: 99%
“…In view of the dependency of GATA-1 Plt13/ϩ mast cells on stimulation by the combination of SCF and IL-3 and the absence of IL-3 in unmanipulated mice (17), the injection of IL-3 might similarly increase mast cell numbers in the Plt13 spleen-the spleen being the most responsive to IL-3 stimulation of mast cell numbers (18). There would also be merit in examining the allelic type of tissue mast cells developing in Plt13 mice in response to worm infestation (19,20) to establish whether GATA-1 Plt13 mast cells were able to take part in such responses.…”
Section: Discussionmentioning
confidence: 99%
“…6). In the mouse, CD40d mediates mast cell adhesion to endothelium and is important for mast cell immigration into the small intestine during nematode infection [36]. huMC up-regulated genes involved in antigen presentation such as CD80 (Fig.…”
Section: Discussionmentioning
confidence: 99%